Substitution of equations for evaluation of energy consumption in rotor-stator mixers - Олександр Семінський (Mechanics and Advanced Technologies, 2022)
In the presented publication, an attempt to develop the theory of mixing by considering rotor-stator mixers from the standpoint of mechanical mixing devices was made.